The impact of ventricular-arterial coupling on aerobic capacity across the heart failure spectrum. (3rd October 2022) - Pugliese, N R; Balletti, A; Armenia, S; De Biase, N; Faita, F; Mengozzi, A; Paneni, F; Ruschitzka, F; Virdis, A; Ghiadoni, L; Taddei, S; Williams, B; et al.
Abstract: Background: Ventricular-arterial coupling (VAC) can be evaluated as the ratio between arterial stiffness (pulse wave velocity, PWV) and myocardial deformation (global longitudinal strain, GLS). Objectives: To evaluate VAC across the spectrum of heart failure (HF). Methods: We introduced a Doppler-derived, single-beat technique to estimate aortic arch PWV (aa-PWV) in addition to tonometry-derived carotid-femoral PWV (cf-PWV). We measured PWVs and 3D-GLS in 155 healthy controls, 75 subjects at risk of developing HF (American College of Cardiology/American Heart Association Stage A-B) and 236 patients in HF Stage C with preserved (HFpEF, n=104) or reduced ejection fraction (HFrEF, n=132). We evaluated peak oxygen consumption (VO2) and peripheral extraction (AVO2diff) using combined cardiopulmonary-echocardiography exercise stress. Results: aa-PWV was obtainable in all subjects and significantly lower than cf-PWV in all subgroups (p<0.01). PWVs were directly related and increased with age (all p<0.0001). cf-PWV/3D-GLS was similarly compromised in HFrEF (1.08±0.36) and HFpEF (1.05±0.22), while aa-PWV/3D-GLS was more impaired in HFpEF (0.69±0.11) than HFrEF (0.60±0.15; p<0.01). Stage A-B had values of cf-PWV/3D-GLS and aa-PWV/3D-GLS (0.66±0.25 and 0.47±0.12) higher than controls (0.47±0.10 and 0.40±0.10) but lower than Stage C (all p<0.01). Peak AVO2diff was inversely related with cf-PWV/3D-GLS and aa-PWV/3D-GLS (all p<0.01). cf-PWV/3D-GLS and aa-PWV/3D-GLS independently predicted peak VO2 in the overall population (adjusted R2=0.32 and 0.35; all p<0.0001) but only aa-PWV/3D-GLS was independently associated with flow reserve during exercise (R2=0.51; p<0.0001). Conclusion: Abnormal VAC is directly correlated with greater severity of HF and worse functional capacity. HFpEF shows a worse VAC than HFrEF when expressed by aa-PWV/3D-GLS. Funding Acknowledgement: Type of funding sources: None.